Parents’ Beliefs About the Benefits and Detriments of Mobile Screen Technologies for Their Young Children’s Learning: A Focus on Diverse Latine Mothers and Fathers - Ochoa, Wendy; Reich, Stephanie M. (Frontiers in Psychology, 2020)
Young children’s use of mobile screens is increasing despite the American Academy of Pediatrics’ recommendations to limit screen use (Reid et al., 2016). Research on TV has found that maternal beliefs about the effects of screens on children’s learning and parental socioeconomic status influence children’s media consumption. However, few studies have explored parents’ beliefs about mobile screens and whether there are differences in beliefs by socioeconomic status, particularly among the largest minoritized group— Latines. Because Latines are a socioeconomically and linguistically heterogenous group, but are often represented by low-income mothers in research, it is important to understand whether there are socioeconomic and linguistic differences on how and why Latine mothers AND fathers permit their children to use mobile screens. This study used in-depth, semi-structured interviews to understand how and why Latine mothers (low-income=10, middle-to-high income=10) and fathers (low-income=10, middle-to-high income=10) permitted their children (0-4 years) to use mobile screens. Specifically, we discussed their beliefs about how mobile screens support and hinder their children’s learning and how their children used them. Results from qualitative content analysis showed that mothers and fathers, across income, education levels, and language use, believed that they, as parents, were the key decision-makers in determining the extent to which mobile screens supported and hindered their young children’s learning. They described mediation strategies of selecting appropriate content, setting time limits, and monitoring use, to ensure that their children primarily benefitted from device use. However, two distinctions were noted. Parents with a high school diploma or beyond stressed the importance of co-using devices with their children. This was not mentioned by less formally educated parents. Additionally, low-income parents with diverse educational levels, mentioned the importance of continuously monitoring device use to avoid their children encountering inappropriate content. Findings can inform work seeking to promote optimal media habits among Latine families.